Project Management Information Systems: a Systematic Review - Massimo, Rebuglio; Zenezini, Giovanni; Ottaviani, Filippo Maria; De Marco, Alberto (Procedia computer science, 2025)
This paper presents a systematic scientific literature review of software in Project Management over the past five years. Through keyword-based research and subsequent selection, 108 papers were identified. Initially, these papers were categorized based on their research methodology and objectives. Then, trends related to the terminology, affiliation country, and journals and conferences where they were published were analyzed. The first result is related to the nomenclature: most sources refer to this kind of software as Project Management Information System (PMIS), followed by Project Management Software (PMS), Project Management System, and Project Management Tools. As for the contents, those include 43 case studies and/or technical reports on PMIS development, 28 case studies about implementing PMIS in business contexts, 27 frameworks and models for developing or implementing a PMIS, 13 models for comparing PMIS, and 12 surveys on PMIS adoption (some sources fall into multiple categories). No specific trending journals or conferences have emerged. It is discussed that the lack of standardized terminology has hindered the development of coherent literature strands, unlike in other business software domains such as Enterprise Resource Planning (ERP). This fragmentation could act as a barrier to competition among applications, delaying the development of quality software and necessitating customized solutions due to the scarcity and difficulty of obtaining commercial options.